2018
DOI: 10.21037/jtd.2018.04.07
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer early detection and health disparities: the intersection of epigenetics and ethnicity

Abstract: Lung cancer is the most prominent cause of cancer-related mortality. Significant disparities in incidence and outcome characterize the disease's manifestations among ethnically and racially diverse populations. Complete surgical resection is the most effective curative treatment. However, success relies on early tumor detection. The National Lung Cancer Screening trial showed that lung cancer related mortality can be reduced by the use of low-dose CT (LDCT) screening. However, this test is plagued by a high fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 101 publications
(111 reference statements)
0
10
0
Order By: Relevance
“…For example, Fu et al (2014) showed that the VDR Bsm1 polymorphism played a protective role in the lung carcinogenesis, while Zhong et al (2014) found that B allele and bb genotype were associated with lung cancer risk in overall populations. Furthermore, lung cancer rates and trends vary substantially by sex, age, race/ethnicity, socioeconomic status, and geography (de Groot et al, 2018;Lerner et al, 2018). Genetic and environmental factors may also influence the VDR and GC plasma concentrations and functions (Wilson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Fu et al (2014) showed that the VDR Bsm1 polymorphism played a protective role in the lung carcinogenesis, while Zhong et al (2014) found that B allele and bb genotype were associated with lung cancer risk in overall populations. Furthermore, lung cancer rates and trends vary substantially by sex, age, race/ethnicity, socioeconomic status, and geography (de Groot et al, 2018;Lerner et al, 2018). Genetic and environmental factors may also influence the VDR and GC plasma concentrations and functions (Wilson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While it is likely that most pathways may remain consistent between groups, it is possible that exposure and access to different factors, including different biological, environmental, and socioeconomic conditions, may contribute to differential epigenetic changes, leading to racial disparities in lung cancer outcomes among AAs ( 39 41 ). And yet, specific mechanisms through which how neighborhood conditions may contribute to epigenomic changes and gene expression have been far less explored ( 42 ).…”
Section: Epigenetics In Lung Cancer Disparitiesmentioning
confidence: 99%
“…Recent research in comparative epigenetics in the U.S. reveals a spectrum of promoter methylation across racial/ethnic groups, the body of studies published in the literature about epigenetics in cancer in minority populations is scarce. Many studies often do not indicate race-specific changes in DNA methylation ( 42 , 46 , 47 ). However, there has been progress.…”
Section: Epigenetics In Lung Cancer Disparitiesmentioning
confidence: 99%
“…To date, imaging is still the major diagnostic technique for lung cancer. Although there are some biomarkers such as CEA or CA125, the lack of specificity and sensitivity inhibits their broad uses, thus demanding the need for better biomarkers [124].…”
Section: Glycans As Potential Biomarkers In Cancermentioning
confidence: 99%